Pemanfaatan Panas Buang Atap Seng dengan Menggunakan Generator Termoelektrik sebagai Sumber Energi Listrik Terbarukan: Indonesian - Aby Elsa Putra; Rifky Rifky; Agus Fikri (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2018)
This research was conducted to utilize waste heat energy zinc roof for a revamped into a source of electrical energy. Waste heat utilization of zinc using thermoelectric generator type of TEC-12706 to convert thermal energy into electrical energy and the fan with speed 5 m/s to hold a low temperature in a cold area of heatsink. This research was conducted using a test simulation tool made by zinc, aluminum and acrilic. Waste heat utilization of testing zinc roof done starting at 09.00 WIB until 15.00 WIB for 3 days, with some measured parameters required as the intensity of solar radiation (Es), airspeed (v), current (I), power (W) and temperature (T) some of which are found in the system tools of simulation testing. From the results of testing performed, the value of the highest efficiency i.e. of 0,00888% and the largest electrical power generated in the amount of 0,0042 W. A high intensity of the solar radiation it will affect the temperature of the environment which will also have an effect on the temperature in the cold area of heatsink, then the value of the temperature difference will also be affected. Heat resistance value on the system also affects the value of the waste heat energy can be changed into electrical energy.